Polymorphism of the 3' open reading frame of the virus associated with the acquired immune deficiency syndrome, human T-lymphotropic virus type III. - Ratner, L (1985)
The genome of the virus associated with the acquired immune deficiency syndrome (AIDS), human T-lymphotropic virus type III (HTLV-III), includes two open reading frames, not found in other retroviruses. One of these, designated 3' open reading frame (3'orf) is 648 base pairs (bp) in length, and overlaps with the 3' long terminal repeat (LTR) sequences. Sequences of additional HTLV-III clones were determined in order to estimate the level and location of variation within 3'orf, to gain some insight into the function of its protein product. Newly determined sequences are reported for 3'orf of two unintegrated clones of HTLV-III and three cDNA clones made from virion RNA derived from the same cell line infected with pooled blood samples of different patients with AIDS or AIDS-related complex symptoms (ARC). In addition, sequences for 3'orf were derived from an unintegrated viral clone derived from a different cell line infected with a distinct isolate from a single patient. These sequences are compared to those previously reported for six other viral clones. Sequences of 3'orf differ among clones by 1.1-10.4% bp and 2.4-17.0% of predicted amino acids. This represents significantly greater sequence variation than is found in the entire genome on average. Moreover, a functional proviral clone has a termination codon at amino acid residue 124 of this open reading frame. This raises questions concerning the structure, and regulation of expression of the protein encoded by 3'orf.